Empirical analysis of borrowers' motivation to use online peer-to-peer lending platforms in India. (26th January 2023) - Gupta, Sagar; Mahajan, Jayant; Godwin, Benny J.
Established on the technology acceptance model, this paper puts forward a model to understand the borrowers' motivation to use (MU) peer-to-peer (P2P) lending platforms. Data from 362 Indian users were employed to test the research model by applying structural equation modelling. The results show that perceived intention, ease of use, and usefulness have significant relation in motivating borrowers to use P2P lending platforms. However, borrowers' perceptions of trust had an insignificant impact on MU the P2P lending platform. When compared to the individual technology acceptance model, the integrated model provides further explanation regarding the motivation of borrowers to use P2P lending platforms. The study contributes to the theoretical area by identifying the factors that motivate borrowers to use P2P lending platforms for their short-term financial requirements, from a unified perspective. In addition, this research provides insights about borrowers' MU P2P lending platforms in India.